Influenza virus matrix protein M1 interacts with SLD5 to block host cell cycle. (16th May 2019) - Zhu, Li; Zhao, Wenming; Lu, Jiao; Li, Shan; Zhou, Kai; Jiang, Wei; Duan, Xuefeng; Fu, Lifeng; Yu, Bolan; Cai, Kathy Q.; Gao, George Fu; Liu, Wenjun; et al.
Abstract: Influenza virus matrix 1 protein (M1) is highly conserved and plays essential roles at many stages of virus life cycle. Here, we used a yeast two‐hybrid system to identify the host protein SLD5, a component of the GINS complex, which is essential for the initiation of DNA replication in eukaryotic cells, as a new M1 interacting protein. M1 from several different influenza virus strains all interacted with SLD5. Overexpression of SLD5 suppressed influenza virus replication. Transient, stable, or inducible expression of M1 induced host cell cycle blockade at G0/G1 phase. Moreover, SLD5 partially rescued M1 expression‐ or influenza virus infection‐induced G0/G1 phase accumulation in cell lines and primary mouse embryonic fibroblasts. Importantly, SLD5 transgenic mice exhibited higher resistance and improved lung epithelial regeneration after virus infection compared with wild‐type mice. Therefore, influenza virus M1 blocks host cell cycle process by interacting with SLD5. Our finding reveals the multifunctional nature of M1 and provides new insight for understanding influenza virus–host interaction.